1991
DOI: 10.1002/hup.470060209
|View full text |Cite
|
Sign up to set email alerts
|

Fengabine in depression: A placebo‐controlled study of a GABA agonist

Abstract: A double-blind controlled trial of Fengabine, a GABA agonist, against placebo was carried out in outpatient major depressives. Subjects were treated for up to 6 weeks with Fengabine three times daily, using 900 mg daily in the first week and 1800 mg daily thereafter. A total of 49 subjects were included, of whom 32 completed 6 weeks. Efficacy analyses showed no evidence of superiority of active drug over placebo, and the two groups were closely comparable throughout the study. Fengabine was free of subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Neither agent proved to be superior to placebo. 70 Although many antidepressants block GABAa receptors and despite advancement of a GABAA-ergic predominance hypothesis for depression,71 recent attention has focused upon the GABAb receptors.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Neither agent proved to be superior to placebo. 70 Although many antidepressants block GABAa receptors and despite advancement of a GABAA-ergic predominance hypothesis for depression,71 recent attention has focused upon the GABAb receptors.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Other papers (e.g. review articles, letters) in which the CID was used or cited will not be discussed in detail [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. …”
Section: Resultsmentioning
confidence: 99%
“…The mixed GABA A and GABA B agonist, progabide, may have antidepressant properties in patients with major depression (Lloyd et al 1983). Another mixed GABA agonist, fengabine, was as effective as tricyclic antidepressants in the treatment of depression in some studies (Magni et al 1989;Nielsen et al 1990), although no more effective than placebo in another (Paykel et al 1991). Interestingly, while benzodiazepines are not thought to have striking antidepressant effects when used alone, a recent meta-analysis has demonstrated that when used in combination with antidepressant medication they increase both the efficacy and tolerability of treatment (Furukawa et al 2001).…”
Section: Changes In Gaba With Treatment Of Mood Disordermentioning
confidence: 99%